Evidence for elevated emissions from high‐latitude wetlands contributing to high atmospheric CH4 concentration in the early Holocene. Issue 1 (19th February 2013) - Yu, Zicheng; Loisel, Julie; Turetsky, Merritt R.; Cai, Shanshan; Zhao, Yan; Frolking, Steve; MacDonald, Glen M.; Bubier, Jill L.
<x xml:space="preserve">Abstract</x> [1] The major increase in atmospheric methane (CH4) concentration during the last glacial‐interglacial transition provides a useful example for understanding the interactions and feedbacks among Earth's climate, biosphere carbon cycling, and atmospheric chemistry. However, the causes of CH4 doubling during the last deglaciation are still uncertain and debated. Although the ice‐core data consistently suggest a dominant contribution from northern high‐latitude wetlands in the early Holocene, identifying the actual sources from the ground‐based data has been elusive. Here we present data syntheses and a case study from Alaska to demonstrate the importance of northern wetlands in contributing to high atmospheric CH4 concentration in the early Holocene. Our data indicate that new peatland formation as well as peat accumulation in northern high‐latitude regions increased more than threefold in the early Holocene in response to climate warming and the availability of new habitat as a result of deglaciation. Furthermore, we show that marshes and wet fens that represent early stages of wetland succession were likely more widespread in the early Holocene. These wetlands are associated with high CH4 emissions due to high primary productivity and the presence of emergent plant species that facilitate CH4 transport to the atmosphere. We argue that early wetland succession and rapid peat accumulation and expansion (not simply initiation) contributed to high CH4 emissions from northern regions, potentially contributing to the sharp rise in atmospheric CH4 at the onset of the Holocene.